MAL MEDIS DI MAKASSAR DENGAN PENDEKATAN BANGUNAN SEHAT - Nurpuspitasari, Nurpuspitasari; Arfan, Taufik; Mutmainnah, Mutmainnah (Nature : National Academic Journal of Architecture, 2014)
These planning and designing are aimed to design Medical Mall in Makassar with healthy building approach, although in macro such as deciding the location and footprint, and also in micro such as deciding the form and its appearance, program, measuring rooms and relating each rooms, structure, material, until its equipments. The method which is used is Descriptive, the data comes from secondary data, those are literature study through books, short papers, references, standard, internet and others written sources that is related with planning and designing Medical mall in Makassar with healthy building approach. The results of these designing are creating a place in servicing health and others facilities supporting medical health in a integrated building, that is based comfortable and save environment fulfill requirements of physiological, psychological and free from spreading diseases.